Elaboration of the Monument to V. I. Lenin in Ulan-Ude: Pages of History - Sharavina, Arina; Kulesh, Victor (project baikal, 2019)
The article describes the history of the creation of the monument to V. I. Lenin, as well as designing and development of the central Square of Soviets in Ulan-Ude. It features design proposals and the process of elaboration of the final version, as it is today.
Keywords: Ulan-Ude; monument to V. I. Lenin; Square of Soviets; Buryatgrazhdanproject Institute; V. I. Kulesh